2014
DOI: 10.1111/age.12178
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression in livestock species: review and meta‐analysis

Abstract: Inbreeding, by virtue of its consequence on traits of interest, is a topic of major interest for geneticists and animal breeders. Based on meta-analysis conducted on 57 studies and seven livestock species considering a wide variety of selected traits, it was estimated that inbreeding depression corresponds to on average a decrease of 0.137 percent of the mean of a trait per 1 percent of inbreeding. The decrease was larger for production traits (reduction of 0.351%) than for other trait categories. For populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(220 citation statements)
references
References 83 publications
10
195
0
15
Order By: Relevance
“…Several studies on livestock species have shown the heterogeneity of inbreeding depression with neutral or negative or positive effects on different traits (Leroy 2014). As reported by Barczak et al (2009), in a given population "bad" and "good" inbreeding effects are mixed.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Several studies on livestock species have shown the heterogeneity of inbreeding depression with neutral or negative or positive effects on different traits (Leroy 2014). As reported by Barczak et al (2009), in a given population "bad" and "good" inbreeding effects are mixed.…”
Section: Resultsmentioning
confidence: 93%
“…Inbreeding depression has been investigated through a large variety of models and hypotheses according to the type of available data (Leroy 2014). Inbreeding depression can be estimated as a linear doi: 10.17221/8664-CJAS regression coefficient between a phenotypic value and inbreeding coefficient computed by genealogical data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in livestock populations, regression of individual performance on F PED of each animal is the most frequent procedure applied (Kristensen and Sorensen, 2005;Leroy, 2014). Although widely applied, the methodology has several critical points, some related to the statistical analysis and the other related to the estimation of inbreeding, which should be taken into account when interpreting results.…”
Section: Classical Approach Of the Inbreeding Depression Estimationmentioning
confidence: 99%
“…In contrast, inbreeding depression is originally defined for the quantitative trait with no sampling variation in the inbreeding level for individuals with the same F PED (for example, all littermates have the equal F PED ) and with the rate of inbreeding at selected loci that is expected to be the same as at neutral loci. Thus, estimation of inbreeding depression based on F PED (Kristensen and Sorensen, 2005;Casellas et al, 2009;Leroy, 2014) was perfectly adapted for the infinitesimal model (Fisher, 1918). Unfortunately, infinitesimal model (modification with dominance) does not correspond well to the inheritance of all traits, particularly traits controlled by a finite number of loci (Curik et al, 2001(Curik et al, , 2002.…”
Section: Genomic Analysis Of the Negative Consequences Of Inbreedingmentioning
confidence: 99%